Mannanoligosaccharides in diets for nursery pigs - C L Jones; C W Starkey; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 168 pigs (average initial BW of 13.2 lb and avg initial age of 21 d) was used in a 35-d experiment to determine the effects of mannanoligosaccharides on growth performance of nursery pigs fed diets without antibiotics. Treatments were: 1) a positive control with carbadox added at 50 g/ton of diet, 2) a negative control without antibiotic, 3) the negative control with mannanoligosaccharides from dried Saccharomyces cerevisiae fermentation solubles (Bio-Mos added at 0.2% of the diet), and 4) the negative control diet with mannanoligosaccharides from the cell walls of yeast (Safmannan added at 0.1% of the diet). For d 0 to 7, ADG and F/G was no better (P>0.36) for pigs fed the diet with antibiotic than the other treatments. However, this lack of difference was the result of good growth performance among pigs fed the diets with mannanoligosaccharides vs the negative control (i.e., P0.49). Analyses of fecal samples indicated no effect of any treatment on fecal concentrations of total coliforms and E. coli (P>0.54). In conclusion, we did observe a positive effect of the mannanoligosaccharides on growth performance of weanling pigs that was intermediate to the nonmedicated and medicated control diets. Those effects were not associated with changes in coliform concentrations in the feces and were most likely caused by other physiological effects.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Antimicrobial; Nursery pigs; Mannanoligosaccharides; Swine